DOES INCOME SMOOTHING IMPROVE INFORMATIVENESS OF STOCK PRICES? - Shinta Ningtiyas Nazar; Titik Ekowati; Hery Setiyawan (Jurnal Ilmiah Econosains, 2017)
The purpose of this research is to get empirical evidence from effect Income smoothing  to Informativeness of Stock Prices  in Indonesian Stock Exchange (IDX). Population from this research is take from companies that have been listing Index LQ 45 in IDX form 2003 until 2015. Income Smoothing is masured by Jonesâ€™s Model which have been modified by Kothari et. all (2005).  Informativeness of stock price using Zarowin and Tucker Model (2006) Future Earnings Response Coeficient, and  the relations to earnings persistence, which is can been seen from  relation from current earnings dan future earnings.  The research is using data from year 2003 until 2015 period, and  year 2014 used as terminal year.  That found  income smoothing have a negative effect to informativeness of stock  price and also found  the managersâ€™ income smoothing action always decreases earnings from 2013 to 2015. Current earnings have related to future earnings.